1998
DOI: 10.1002/(sici)1521-4095(199805)10:8<611::aid-adma611>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Single-Shell Nanotubes

Abstract: Purification of single‐shell nanotubes is essential if reliable information about their physical and chemical properties is to be obtained. Using the present synthetic techniques, samples typically contain 30% or more amorphous carbon and catalytic metal particle impurities. An extremely simple and efficient method of purification, involving boiling the nanotubes in concentrated nitric acid, is reported. It is demonstrated that this method removes most of the impurities and, unlike some other methods, is not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(137 citation statements)
references
References 6 publications
1
134
0
1
Order By: Relevance
“…The defect sites that are introduced into the carbon nanotubes can be used to shorten and eventually destroy the carbon nanotubes under similar oxidizing conditions. 55,[79][80][81][82] The shortened tubes (s-SWNTs) are better solvated by amide solvents than are the full-length SWNTs.…”
Section: Dissolutionmentioning
confidence: 99%
“…The defect sites that are introduced into the carbon nanotubes can be used to shorten and eventually destroy the carbon nanotubes under similar oxidizing conditions. 55,[79][80][81][82] The shortened tubes (s-SWNTs) are better solvated by amide solvents than are the full-length SWNTs.…”
Section: Dissolutionmentioning
confidence: 99%
“…An Astex Large Area Diamond Deposition System with a 5 kW microwave source was used. Nanotubes were purified through treatment with nitric acid, following the method of Dujardin et al [49], to remove the remaining catalyst and aggregates. Following purification, the nanotubes were stored in a desiccator.…”
Section: Chemicalsmentioning
confidence: 99%
“…[13][14][15] However, Dujardin et al have suggested that the same purification process would destroy single-wall carbon nanotubes. Dillon et al 16 have described an oxidation process that produces >98 wt % pure SWNTs.…”
Section: Introductionmentioning
confidence: 99%